Processing of null subject in Alzheimer’s disease - Martinho, Maria José J. P. Martinho (2023)
This study focuses on the impact of Alzheimer’s Disease on language, namely the impact in the context of the use of the null subject. We analysed the productions of a group of twelve Alzheimer’s patients and a control group with the same dimension, when reading three types of sentences: One clause with simple tense; one clause with complex tense; two-clause sentences. The sentences, translated from a previous study of Italian and English, were repeated over three days by each of the participants and audio recorded for later data processing. Alzheimer’s patients underperformed when compared to the control group, but some results showed non-significant differences. When the data obtained in the study in Portugal was compared to that from the study conducted in England, it was concluded that the Alzheimer patients tended to produce more null subjects and that these were more prevalent in longer and complex sentences. The Portuguese participants also presented a tendency for the production of less null subjects than the Italians.